2016
DOI: 10.1111/bju.13517
|View full text |Cite
|
Sign up to set email alerts
|

Robot‐assisted Fallopian tube transection and anastomosis using the new REVO‐I robotic surgical system: feasibility in a chronic porcine model

Abstract: ObjectivesTo evaluate the feasibility and safety of the new REVO-I robotic platform by performing Fallopian tube transection and anastomosis in live porcine models. Subjects and MethodsA prospective chronic animal study was carried out in four crossbred female pigs. The primary outcome was assessment of the pigs' 2-week survival. The secondary outcomes were measurements of intra-operative variables and the complications or difficulties arising when using the REVO-I. ResultsFallopian tube anastomosis was succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 8 publications
0
28
0
Order By: Relevance
“…The da Vinci system's closed console envelops the surgeon's face and can compromise the surgeon's awareness within the operating theater. In contrast, the Telelap ALF‐X and the newer Revo‐i, which is currently undergoing trials in Korea, offer open consoles that can improve operating ergonomics . The Telelap ALF‐X monitor requires the surgeon to wear 3‐D glasses and incorporates eye‐tracking, whereas Revo‐i has a 3‐D HD monitor .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The da Vinci system's closed console envelops the surgeon's face and can compromise the surgeon's awareness within the operating theater. In contrast, the Telelap ALF‐X and the newer Revo‐i, which is currently undergoing trials in Korea, offer open consoles that can improve operating ergonomics . The Telelap ALF‐X monitor requires the surgeon to wear 3‐D glasses and incorporates eye‐tracking, whereas Revo‐i has a 3‐D HD monitor .…”
Section: Discussionmentioning
confidence: 99%
“…The configuration of this model was designed to be similar to the da Vinci Surgical System. Abdel Raheem et al completed a preclinical study with porcine model in 2016 , and a clinical trial to treat patients with radical cholecystectomy or prostatectomy was performed by using this surgical system in 2017 . meerecompany obtained commercialized approval from the Korean Food and Drug Administration in August 2017.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intuitive Surgical currently owns >1500 patents (Appendix 1). Several manufacturers are developing alternative robotic systems (Figs ); however, because of issues related to patenting, in particular, their clinical applications remain limited . Nevertheless, the landscape of robotic surgery is expected to witness significant changes as new technologies might soon become available.…”
Section: Introductionmentioning
confidence: 99%
“…Asian countries like South Korea and China has also developed their own robotic system. Abdel Raheem et al (11) have reported their success in animal study using REVO I robot system (Meree company, Seoul, South Korea) and recently commenced with human trials. In China, Yi et al (12) reported safe and effective outcome of clinical cases utilizing Micro Hand S System.…”
mentioning
confidence: 99%